Antimicrobial Activity of Fungal Extract of The Aspergillus flavus from Hiri Island, North Maluku to Pathogenic Bacteria - Sri Sedjati; Ambariyanto Ambariyanto; Agus Trianto; Endang Supriyantini; Ali Ridlo; Muhammad S. Bahry; Rizky Rifatma Jezzi; Mahadika Fanindhita Sany (Jurnal Kelautan Tropis, 2020)
Antibacterial compounds from sponge association fungi are one of the alternatives to search for new antibiotics against resistant bacteria. This study aims to explore the secondary metabolites potential from sponge association fungi as MDR pathogens antibacterial and to cultivate these fungi using a variety of cultivation media. TE-BO-09.1. Isolate can inhibit 3 bacteria, K. pneumoniae, B subtilis, and S. aureus, but is not able to inhibit E. coli and P. aeruginosa. Cultivation using standard media of Malt Extract Agar (MEA) and media modified from fish broth (M1, M2) and cassava infusion (M3, M4) produce secondary metabolites with varying quantities and antimicrobial activity. The inhibition zone of the produced extract with 500 μg/disc concentration ranged from 7.14 to 10.32 mm. The strongest potential was shown by ethyl acetate extract from isolates cultured with M2 (9 days cultivation), of which is able to produce 10.32 mm inhibition zones against S. aureus and methanol extracts from isolates cultured with M4 (6 days cultivation), and able to produce 10.05 mm inhibition zones against K. pneumoniae. In conclusion, the fungus  Aspergillus flavus can be culture using fish broth added glucose and cassava infusion water added peptone media to potentially produce antibacterial compounds against MDR pathogens.